Racial Disparities in Stroke Readmissions Reduced in Hospitals With Better Nurse Staffing. Issue 1 (January 2022) - Carthon, J. Margo Brooks; Brom, Heather; McHugh, Matthew; Daus, Marguerite; French, Rachel; Sloane, Douglas M.; Berg, Robert; Merchant, Raina; Aiken, Linda H.
Abstract : Background: Racial minorities are disproportionately affected by stroke, with Black patients experiencing worse poststroke outcomes than White patients. A modifiable aspect of acute stroke care delivery not yet examined is whether disparities in stroke outcomes are related to hospital nurse staffing levels. Objectives: The aim of this study was to determine whether 7- and 30-day readmission disparities between Black and White patients were associated with nurse staffing levels. Methods: We conducted a secondary analysis of 542 hospitals in four states. Risk-adjusted, logistic regression models were used to determine the association of nurse staffing with 7- and 30-day all-cause readmissions for Black and White ischemic stroke patients. Results: Our sample included 98, 150 ischemic stroke patients (87% White, 13% Black). Thirty-day readmission rates were 10.4% (12.7% for Black patients, 10.0% for White patients). In models accounting for hospital and patient characteristics, the odds of 30-day readmissions were higher for Black than White patients. A significant interaction was found between race and nurse staffing, with Black patients experiencing higher odds of 30- and 7-day readmissions for each additional patient cared for by a nurse. In the best-staffed hospitals (less than three patients per nurse), Black and White stroke patients' disparities were no longer significant. Discussion: Disparities in readmissions between Black and White stroke patients may be linked to the level of nurse staffing in the hospitals where they receive care. Tailoring nurse staffing levels to meet the needs of Black ischemic stroke patients represents a promising intervention to address systemic inequities linked to readmission disparities among minority stroke patients. Abstract : Supplemental digital content is available in the text.